1993
DOI: 10.1007/bf00375067
|View full text |Cite
|
Sign up to set email alerts
|

Fast and slow blockades of the inward-rectifier K+ channel by external divalent cations in guinea-pig cardiac myocytes

Abstract: The present patch-clamp study shows that external Mg2+, Ca2+ and Sr2+ decrease the unit amplitude of inward current through the inward-rectifier K+ channel in a concentration-dependent manner. Sr2+ produces a voltage-dependent flickering block as well, and the fractional electrical distance between the external orifice and the Sr2+ binding site (delta) is 0.73. The decrease of unit amplitude is reversible and voltage independent while it does not increase the noise level on the open-channel current. Unit curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
8
25
0
1
Order By: Relevance
“…9) (Shioya, Matsuda & Noma, 1993), it is difficult to produce the shift of the time constant. Therefore, we speculate that the shift of the time constant was caused by the decrease in the transmembrane potential through screening the fixed negative charges on the membrane surface or at the channel orifice.…”
Section: Discussionmentioning
confidence: 99%
“…9) (Shioya, Matsuda & Noma, 1993), it is difficult to produce the shift of the time constant. Therefore, we speculate that the shift of the time constant was caused by the decrease in the transmembrane potential through screening the fixed negative charges on the membrane surface or at the channel orifice.…”
Section: Discussionmentioning
confidence: 99%
“…The voltage dependence has led to the suggestion that the ions block the channel by binding to a site within the channel pore. In guinea-pig ventricular cells, Biermans et al (1987) and Shioya et al (1993) showed that extracellular cations normally present in the extracellular fluid (Mg¥ and Ca¥) block the inward rectifying K¤ current IK1. During hyperpolarizing pulses, Kir2.1 current shows a time-dependent inactivation and Kubo et al (1993a) suggested that this is due to channel block by cations present in normal extracellular fluid.…”
mentioning
confidence: 99%
“…The lindane-increased I out cannot be attributed to the opening of lindane-induced ionic channels since lindane has been shown to be devoid of ionophoretic properties in planar lipid bilayers [9]. Our data show that the lindane-increased I out still persists in the presence of Sr 2+ which is known to block the background I K1 [12] and I K-Ca [13] currents in cardiac tissues. Our findings reveal that quinidine inhibits the effect of lindane on I out .…”
Section: Discussionmentioning
confidence: 67%